Kadar Leptin Balita Stunting yang Diberi Makanan Tambahan Berbasis Daun Kelor dan Ikan Laut - Fatiah, Nirmala Al; Yuniastuti, Ari; WH, Nugrahaningsih; Lisdiana, Lisdiana (Universitas Negeri Semarang, 2024)
Leptin plays a role in regulating the growth of bones and other body tissues. Leptin can affect the epiphyseal growth zones in long bones, contributing to height growth. The aim of this research is to analyze leptin levels and body height in toddlers before and after giving additional food based on Moringa leaves and sea fish. The supplementary feeding intervention was carried out for 10 weeks on 30 toddlers with stunted and very stunted nutritional status at the Sedan Community Health Center, Rembang Regency. Leptin levels in the blood were analyzed using ELISA, height measurements were carried out using a stadiometer, determination of nutritional status was guided by the PERMENKES regarding 2020 child anthropometry standards, and data analysis used the SPSS program. The results of the study showed that the average leptin level decreased and the average body height increased after the intervention of providing additional food based on Moringa leaves and sea fish. Thus, it can be concluded that decreasing leptin levels can cause a decrease in fat and adipogenesis which results in increased bone formation in the form of increased height in stunted toddlers at the Sedan Community Health Center, Rembang Regency.